Metode pembelajaran ilmu pengetahuan sosial di Sekolah Dasar Negeri 019 Tambusai Utara Kabupaten Rokan Hulu - Prayogi, Ryan; Aida, Welven; Melinda, Cecilia; Rahmawati, Ilham; Hardianto; Betria, Ike (Jurnal Pendidik Indonesia, 2021)
In today's era of education, the challenge for teachers to understand students' characteristics that align with the changing times has become increasingly urgent. This is especially pertinent in teaching Social Sciences (IPS) at the elementary school level, where shaping behaviours and attitudes in line with Pancasila values takes centre stage. This research analyses teaching methods to enhance students' comprehension of the IPS subject within the classroom environment. The research methodology employed is a qualitative approach through a literature review, allowing for collecting information from various sources related to relevant teaching methods. The research findings reveal that several effective methods for enhancing students' understanding include Contextual Teaching and Learning (CTL), which connects learning concepts with everyday life; Cooperative Learning, which fosters interaction among students; Group Discussions to develop speaking and listening skills; Question and Answer sessions to stimulate critical thinking; Role Playing to understand different perspectives; and Field Trips (Karyawisata) for experiential-based learning. This research is expected to provide valuable guidance for teachers in creating engaging and meaningful learning experiences, with the potential to overcome boredom and foster creative thinking patterns among students within the classroom.